Multis vocibus de lingua anglica: towards an outline of an emotional profile of English as a major globalizing natural language of today - Puppel, Stanisław (Scripta Neophilologica Posnaniensia, 2018)
Multis vocibus de lingua anglica: towards an outline of an emotional profile of English as a major globalizing natural language of today